Beyond too little, too late and too much, too soon: a pathway towards evidence-based, respectful maternity care worldwide. Issue 10056 (29th October 2016) - Miller, Suellen; Abalos, Edgardo; Chamillard, Monica; Ciapponi, Agustin; Colaci, Daniela; Comandé, Daniel; Diaz, Virginia; Geller, Stacie; Hanson, Claudia; Langer, Ana; Manuelli, Victoria; Millar, Kathryn; et al.
Summary: On the continuum of maternal health care, two extreme situations exist: too little, too late (TLTL) and too much, too soon (TMTS). TLTL describes care with inadequate resources, below evidence-based standards, or care withheld or unavailable until too late to help. TLTL is an underlying problem associated with high maternal mortality and morbidity. TMTS describes the routine over-medicalisation of normal pregnancy and birth. TMTS includes unnecessary use of non-evidence-based interventions, as well as use of interventions that can be life saving when used appropriately, but harmful when applied routinely or overused. As facility births increase, so does the recognition that TMTS causes harm and increases health costs, and often concentrates disrespect and abuse. Although TMTS is typically ascribed to high-income countries and TLTL to low-income and middle-income ones, social and health inequities mean these extremes coexist in many countries. A global approach to quality and equitable maternal health, supporting the implementation of respectful, evidence-based care for all, is urgently needed. We present a systematic review of evidence-based clinical practice guidelines for routine antenatal, intrapartum, and postnatal care, categorising them as recommended, recommended only for clinical indications, and not recommended. We also present prevalence data from middle-income countries for specific clinical practices, which demonstrate TLTL and increasing TMTS. Health-care providers and health systems need to ensure that all women receive high-quality, evidence-based, equitable and respectful care. The right amount of care needs to be offered at the right time, and delivered in a manner that respects, protects, and promotes human rights.